2005
DOI: 10.3156/jsoft.17.615
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic extraction of music with color image scale

Abstract: Keywords :Color − heard − person .Characteristic recognition .Color image scale Co1 . ユtact Address :Ilisao SHIIZUKA Inノ-prtn ' lti(. ・ . s Kvgakuin し 」 厂 live , ・ sit} v σ厂'idu 'ltc ・ 5〔 ・ ' iool M ∫' Tゴ ∫'-画ノ uki − 24 − 2 ∫ノ r" り 1' ん' ' 7-敢 y θ 163 − 8677 , ノ 'it " (ltlE − nlail :shiizuka @cc . kogakuin, ac , jp 2005月0 N 工 工 一 Eleotronio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Further, the impressions that were created were similar even for the classification of music with expressions in color as variables. As suggested by Yamawaki & Shizuka (2005), this investigation evinced a commonality between the impressions created by music and color [6].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Further, the impressions that were created were similar even for the classification of music with expressions in color as variables. As suggested by Yamawaki & Shizuka (2005), this investigation evinced a commonality between the impressions created by music and color [6].…”
Section: Discussionsupporting
confidence: 54%
“…A previous study on the image of PCCS tone illustrated that the PCCS tone can capture a wider range of impressions than hue 2012, Wakata & Saito;2015) [4,5]. Yamawaki & Shizuka (2005) suggested that the visualization of sound and color do not inhabit totally different image spaces [6]. In this study, it was assumed that color can express impression, and the investigation aimed at expressing music through color.…”
Section: Introductionmentioning
confidence: 92%